A regression approach to estimate the relative roles of pollen-versus seed-mediated gene flow under an isolation by distance model - Barrandeguy, Maria Eugenia (2018)
In the present work, a new estimator to be known as rIBD is proposed. The proposed estimator indirectly quantifies the relative role of gene flow mediated by pollen in relation to the gene flow mediated by seeds in hermaphrodite angiosperm species when an isolation by distance model is assumed. The proposed estimator complements the well-known estimator proposed by Ennos, which is appropriate for studies under the island model. In the present work, the proposed rIBD index was used to analyze microsatellite data from uni- and biparentally inherited genomes generated by simulations, as well as for the analysis of an empirical data set obtained from public databases of forest tree species. The differences in median values of the proposed rIBD index for simulated data using the Stepping Stone Model and Truncated Pareto Distribution Model coincided with the magnitude expected in terms of differences between levels of pollen and seed dispersion previously established in the simulations. In empirical data, the proposed rIBD index shows lower levels of gene flow by seed versus gene flow by pollen, the ratio between them being three times lower than the ratio obtained by the Ennos index estimated under the island model. From the analyses carried out, it is feasible to consider the rIBD index as a suitable estimator of the role of gene flow by seeds in relation to gene flow by pollen under isolation by distance.